Chemistry inspired by nature: macrocyclic pseudopeptides design - Martí-Centelles, Vicente (2013)
The molecular design based on the imitation of the complex structures and processes found in nature is known as bioinspired Chemistry or biomimetic Chemistry. An approach used in this discipline is the preparation of macrocyclic pseudopeptidic compounds from natural amino acids and abiotic components. Proteins exist in nature with very specific properties encoded by the diverse structural and conformational information of the amino acids side chains. The use of this information is a key factor in the design of pseudopeptides with well-defined properties. Therefore, a suitable structural design to obtain the desired functionality relies on the appropriate choice of structural components, natural and abiotic.